Analysis and Experimental of HXD1 Electric Locomotive Steps Fracture - WANG Linfeng; CHEN Guosheng; CHEN Qingming; TAO Gongquan (机车电传动)
The investigation processes and results of the electric locomotive steps fracture were presented. A locomotive suffered from serious vibration problem was chosen for the test and its normal operations were kept during the test. The wheel out-of-roundness (OOR) and vibrations of key components including the step, the axle box, and the bogie frame were measured before and after wheel re-profiling. The wheel OOR measured results indicated that the wheels exhibited the OOR with 12 to 19 orders before re-profiling, i.e. with a center wavelength of 200 mm in the 1/3 octave bands. And the 16 to19 orders OOR became to be dominant after re-profiling, so the wheel polygonal wear could not be absolutely removed by the wheel re-profiling. The vibration measured results showed that the step, the axle box and the bogie frame vibrated with the same dominant frequency before re-profiling,the dominant frequency of the vibration was approximately equal to the passing frequency of a polygonal wheel. The step had natural frequencies ranging from 70 Hz to 90 Hz,the wheel OOR passing frequencies coincided with the step natural frequencies when the running speed range was from 50- 80 km/h. So, the resonance of the step induced by the wheel OOR was the root cause of the fracture.